Computer Aided Resolution of Molecular Conformations - Barry, C. David; University of Oxford (1970)
Silent film demonstrating an early (1970s) computer program for creating three-dimensional molecular models and allowing users to manipulate those models using keyboard commands and a trackball. This film includes the keyboard commands used to operate the software, as well as demonstrations of different functions, views, and display options. The software was created at the Laboratory of Molecular Biophysics at Oxford University, likely, or at least in part, by C. David Barry.
Keywords: Computer simulation; Molecular structure; Molecular structure--Computer programs; Molecular structure--Computer simulation